Gender Analysis of Budget Fraud Through E-Budgeting: An Experimental Study - Samuel Simanjuntak Oliver; Ayu Purnama Ida; Rizki Hardiana Hely (SHS Web of Conferences)
Budget submission is an essential part of an organization. Fraud that occurs in the budget submission process is one of the critical causes of worsening organizational performance. Knowing the causes of budget fraud is a preventive step in preventing fraud in the budget submission process. This study takes a gender perspective to examine its influence on budget slack. Applying an experimental method, the findings of this study successfully confirm previous studies that women tend to be more dishonest than men in budget submission